Franciscan Charism in Higher Education, The - McKelvie, Roberta A. (Spirit and life (Saint Bonaventure, N.Y.), 1992)
This volume addresses the contribution of Franciscan ideals to the institutions of higher learning. The contributors are all experienced in the field of education and present a variety of topics appropriate to formation in that venue.